Efektivitas Pemungutan Retribusi Terminal Pada Dinas Perhubungan Kabupaten Majalengka Tahun 2019-2021 - Sri Nurmayanti; Dedeng Yusuf Maolani (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2022)
This study aims to determine how effective the collection of Terminal levies at the Majalengka Regency Transportation Service is in 2019-2021. The method used by the author is a type of descriptive research with a qualitative approach. Sources of data come from primary data and secondary data. Data collection techniques used in this study were interviews and Documentation Studies. Data analysis techniques in this study used data analysis techniques according to Miles and Huberman, namely data reduction, data presentation and conclusions. The results showed that the effectiveness of collecting terminal fees at the Majalengka Regency Transportation Service in 2019, was measured using the theory (Wulandari & Iryane, 2017) that the adequacy and elasticity criteria did not meet the effective criteria because although population growth in Majalengka Regency increased, it did not match the increase terminal retribution income and for the overall justice dimension have not met the effective criteria, because justice is only limited to levy collection rates according to the principle of justice, but not with retribution collections that are not in accordance with the benefits received by terminal service users, except for the administrative capacity dimension that meets the criteria effective.